Measurement of beauty-quark production in pp collisions at √s = 13 TeV via non-prompt D mesons - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Nath, Abhishek; et al. (Journal of high energy physics, 2024)
The p(T)-differential production cross sections of non-prompt D-0, D+, and D+ s mesons originating from beauty-hadron decays are measured in proton-proton collisions at a centre-of-mass energy root s = 13TeV. The measurements are performed at midrapidity, |y| < 0.5, with the data sample collected by ALICE from 2016 to 2018. The results are in agreement with predictions from several perturbative QCD calculations. The fragmentation fraction of beauty quarks to strange mesons divided by the one to non-strange mesons, f(s)/(f(u)+ f(d)), is found to be 0.114 +/- 0.016 (stat.) +/- 0.006 (syst.) +/- 0.003 (BR) +/- 0.003 (extrap.). This value is compatible with previous measurements at lower centre-of-mass energies and in different collision systems in agreement with the assumption of universality of fragmentation functions. In addition, the dependence of the non-prompt D meson production on the centre-of-mass energy is investigated by comparing the results obtained at root s = 5.02 and 13TeV, showing a hardening of the non-prompt D-meson pT-differential production cross section at higher vs. Finally, the bb production cross section per unit of rapidity at midrapidity is calculated from the non-prompt D-0, D+, D-s(+), and Lambda(+)(c) hadron measurements, obtaining d sigma/dy = 75.2 +/- 3.2 ( stat.) +/- 5.2 (syst.)(-3.2)(+12.3) (extrap.) mu b.
Veröffentlicht: 15. Oktober 2024
*The ALICE collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, J. Crkovska, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grundwald, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, F. Schlepper, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. Van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone [und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 30.06.2025